Peran Minat Baca di Perpustakaan dan Disiplin Belajar terhadap Prestasi Belajar Siswa Kelas Atas SDN Ngabeyan 3 Tahun 2016/2017 - Putra, Irlanda Wisma, Drs. Saring Marsudi, SH. M.Pd (2017)
This research aims to (1) Knowing the role of reading interest in the library of student achievement upscale SDN Ngabeyan 3 years 2016/2017. (2) Knowing the role of learning discipline on the achievement of upper class student of SDN Ngabeyan 3 year 2016/2017. (3) Knowing the role of reading interest in libraries and learning discipline on the achievement of upper class students of SDN Ngabeyan 3 years 2016/2017. This type of the research is quantitative research, population in this research there are upper class student, that is class IV, V and VI SDN Ngabeyan 3 year 2016/2017. The sample in this study were 41 students using Proportionate Stratified Random Sampling technique. Data collection techniques used are questionnaires and documentation. The analysis technique used is multiple regression analysis which preceded by prerequisite analysis test. The results showed that: 1) Reading interest in the library can play significant impact on the achievement of upper class students of SDN Ngabeyan 3 years 2016/2017. Based on t test is obtained tcount > ttable is 3.503 > 2.023 and the probability value of significance <0.05 is 0.001 <0.05. 2) The discipline of learning can play a significant impact on the achievement of upper class students of SDN Ngabeyan 3 years 2016/2017. Based on t test obtained tcount> ttable, that is 3.040 > 2.023 and probability value significance <0,05 is 0,004 <0,05. 3) Reading interest in the library and discipline of learning both play a significant role and significant achievement of upper class students SDN Ngabeyan 3 years 2016/2017. Based on F test obtained Fcount> Ftable, that is 24,505> 3,24 and probability value of significance <0,05, that is 0,000 <0,05. The result of determination test (R2) is 0,563 the meaning of this koofesien is that the role given by the combination of reading interest variable in the library and the learning discipline toward the achievement of upper class student of SDN Ngabeyan 3 year 2016/2017 is 56,3% while the rest 43, 7% is influenced by other variables.